2020
DOI: 10.21203/rs.3.rs-17202/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune Landscape in Burkitt Lymphoma reveals M2-macrophage polarization and Correlation between PD-L1 expression and Non-Canonical EBV latency program

Abstract: BACKGROUND: The Tumor Microenviroment (TME) is a complex milieu that is increasingly recognized as a key factor in multiple stages of disease progression and responses to therapy as well as escape from immune surveillance. However, the precise contribution of specific immune effector and immune suppressor components of the TME in Burkitt lymphoma (BL) remains poorly understood.METHODS: In this paper, we applied the computational algorithm CIBERSORT to Gene Expression Profiling (GEP) datasets of 40 BL samples t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The composition and clinicopathological features of our PTLD collective are comparable to published data, although we had a relatively high percentage of polymorphic PTLD with a total of 23/48 cases (48% vs 19% [32]/28% [33]) [4]. Important parameters determining the classification of PTLD are EBV status and the specific immunodeficiency setting [3,5,6,24]. Although the percentage of EBV-negative PTLD after SOT has increased in recent years, the relatively high number of EBV-negative cases after HCT (5/26) is surprising [34] including two unusual EBV-negative cases, a polymorphic PTLD occurring 3 months after HCT and an EBVnegative non-destructive PTLD in the form of plasmacytic hyperplasia occurring 23 months after HCT [6].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The composition and clinicopathological features of our PTLD collective are comparable to published data, although we had a relatively high percentage of polymorphic PTLD with a total of 23/48 cases (48% vs 19% [32]/28% [33]) [4]. Important parameters determining the classification of PTLD are EBV status and the specific immunodeficiency setting [3,5,6,24]. Although the percentage of EBV-negative PTLD after SOT has increased in recent years, the relatively high number of EBV-negative cases after HCT (5/26) is surprising [34] including two unusual EBV-negative cases, a polymorphic PTLD occurring 3 months after HCT and an EBVnegative non-destructive PTLD in the form of plasmacytic hyperplasia occurring 23 months after HCT [6].…”
Section: Discussionsupporting
confidence: 79%
“…The composition of the tumor microenvironment plays a pivotal role in the pathogenesis of tumors and has been shown to be of prognostic importance [14,24,39,40]. Due to the unique immunologic setup in PTLD patients, the characterization of the TME is of great interest and may have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 56 of 70 BLs (80%) were clustered in the DZ-like cluster according to the 53-genes DZ/LZ signature. This finding was of particular interest if we consider that BL represents a rather homogeneous disease as far as the biological features of the malignant clone are concerned, and that the recently reported variability in BL immune landscape ( Granai et al., 2020 ) may configure different microenvironment scenarios more similar to or distinct from the immunologically cold DZ.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, it has been suggested that the tumor microenvironment in EBV-associated lymphomas is rich in PD-1/PD-L1 active engagements, and PD-1 expressing tumor-infiltrating lymphocytes are associated more with EBV-positive tumors [ 78 , 80 ]. A subset of BL samples are characterized by M2-macrophage polarization, activated PD-L1 expression, and non-canonical LMP2A expression in the tumor microenvironment [ 81 ]. EBV-positive DLBCL cells exhausted T-cells and induced their PD-1 expression in vitro; however, introducing a PD-1 blockade can restore T-cell activity [ 82 ].…”
Section: Immunotherapy and Cell Therapy In Ebv-associated Lymphomamentioning
confidence: 99%